ANALYSIS OF WOODEN RESIDENTIAL HOUSE STRUCTURE AGAINST EARTHQUAKE LOAD - I Ketut Agus Asih Adi Arta; Putu Didik Sulistiana; Cokorda Agung Yujana; I Wayan Jawat (Journal of Infrastructure Planning and Engineering, 2024)
Wood material is a construction material that has its own appeal from an aesthetic and architectural point of view, however wood material has various limitations, namely in terms of durability and structural strength when compared to structural materials such as concrete and steel. This research examines the structural behavior of residential houses using glulam wood materials using program analysis software ETABS.  From the results of initial design calculations, the dimensions of the structural elements were obtained, namely beams measuring 25 cm x 40 cm and columns measuring 30 cm x 30 cm. Based on the results of the analysis that has been carried out, it shows that the house structure has met earthquake resistance requirements with maximum inter-story drift of 24.35 mm (below the 26.92 mm limit). The dynamic analysis shows successful mass participation with total mass participation ratios exceeding 90% in all primary directions: 99.11% for translational motion in X-direction (UX), 99.29% for translational motion in Y-direction (UY), and 99.51% for rotational motion about vertical axis (RZ). These results indicate that the structural model adequately captures both lateral and torsional responses of the building under seismic loading.